2018
DOI: 10.1007/s00127-018-1526-x
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities in mental disorders and substance misuse in young adults

Abstract: PurposeTo investigate the association between mental disorders and substance misuse at 30 years of age with gender, socioeconomic position at birth, and family income trajectories.MethodsThe 1982 Pelotas Birth Cohort was used; all 5914 children born alive at hospital were originally enrolled (99.2% of all city births). In 2012, 3701 subjects were located and interviewed (68% retention rate). Mental disorders and substance misuse were assessed, and their prevalence analysed according to gender, socioeconomic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
2
12
0
2
Order By: Relevance
“…As for socioeconomic determinants, our results agree with those of other longitudinal studies that also point to educational levels and income as important determinants of adults' mental health 58,59,60,61,62 , especially in low and middle-income countries 63 . These findings underline the need to improve these two components of socioeconomic status, which are associated mainly with suicide risk.…”
Section: Discussionsupporting
confidence: 90%
“…As for socioeconomic determinants, our results agree with those of other longitudinal studies that also point to educational levels and income as important determinants of adults' mental health 58,59,60,61,62 , especially in low and middle-income countries 63 . These findings underline the need to improve these two components of socioeconomic status, which are associated mainly with suicide risk.…”
Section: Discussionsupporting
confidence: 90%
“…A recent meta-analysis estimated a global 12-month prevalence of common mental disorders (mood disorders, anxiety disorders and substance use disorders) in adults and found a prevalence of 17.6% of any common mental disorders, which was similar in low-and middle-income countries and high-income countries, but tended to be higher in Latin America and the Caribbean (22%) 3 . In Brazil, only few epidemiological studies estimated the prevalence of mental disorders in early adulthood [19][20][21] , and most assessed symptoms of common mental disorders (depression and anxiety) or specific populations (students, teachers, workers) 19 . Studies applying diagnostic interviews in general population found prevalence of mental disorders varying from 14.4% 21 to 29.6% 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Esse fato é um dilema principalmente nos dois últimos anos da faculdade (internato) 27 . Além disso, uma parcela significativa desses estudantes apresenta uma maior vulnerabilidade para problemas mentais, como aqueles com renda familiar mais baixa que moram em comunidades carentes e com altos índices de violência [28][29][30] . Da mesma forma, os migrantes foram, em muitos casos, obrigados a regressar a suas cidades e seus estados na expectativa do retorno às aulas.…”
Section: Discussionunclassified